Wa'ilan and bos: status seeking in Minahasa - Schouten, Maria Johanna Christina (2017)
Discussion of the various expressions of authority in rural Minahasa (North Sulawesi, Indonesia) and the underlying beliefs. Data on the history of the region and episodes of the author’s fieldwork are provided. Particular attention is paid to the status attributes, the festivities and the burial customs for persons with great authority.